Studies of Meiotic Behaviors in Some Taxa of the Nepalese Papilionaceae - Manandhar, Laxmi; Sakya, Shyam Ratna (Journal of Natural History Museum, 2015)
This paper reports studies of meiotic behaviors of seventeen species, sub-species and varieties in seven genera of the Nepalese Papilionaceae and new chromosome numbers for three species (Crotalaria cytisoides Roxb. ex DC (n=8), Parochetus communis Buch-Ham. ex D. Don (n=8) and Piptanthus nepalensis (Hook.) D. Don. (n=9, 18) are new number reports. Meiotic behaviors are often normal in all the species). However, a few aberrations like univalents, chromosome bridges, laggards, precocious chromosomes and/ or cytomixis have been observed in most of the taxa. Pollen fertility is high (more than 80%) indicating that the abnormalities had not reached mature stages. J. Nat. Hist. Mus. Vol. 26, 2012: 68-79